Is childhood interstitial lung disease (chILD) still a mystery in infants? - Śliwińska, Martyna A.; Rakuś-Kwiatosz, Anna; Szawłoga, Tomasz (Current Issues in Pharmacy and Medical Sciences, 2026)
Childhood interstitial lung disease (chILD) comprises a heterogeneous group of several hundred disorders that affect not only the pulmonary interstitium, as suggested by the name, but also other components of the respiratory system. The prevalence of chILD remains unclear and depends largely on the data source. Many patients die before a definitive diagnosis is established, which further complicates the estimation of disease incidence in infants.In recent years, increased recognition of chILD has drawn growing attention within the medical community. As a result, these disorders have been classified into two major groups: those presenting in children younger than 2 years of age and those affecting older children. Nevertheless, the diagnostic process remains highly challenging. These diseases are rare, and their onset during the neonatal period is often associated with high mortality before a comprehensive diagnostic evaluation can be completed.Currently, several therapeutic options for chILD are available; however, none ensures consistent treatment success. Ongoing research is exploring novel therapeutic strategies, including stem cell transplantation, which may offer new hope for improving outcomes and survival in patients with chILD in the future.